Implementation of Digital Technology in Industry 5.0 Era - Gregorius Paulus Tahu (Postgraduate, University of Mataram, 2025)
This research discusses the implementation of digital technology in industry 5.0 era. In the digital era, industry is undergoing a fundamental transformation due to the development of digital technology. This research uses the literature review method to analyse trends, benefits, challenges, and strategies related to the implementation of these technologies. The results show that digital technologies, such as internet banking, mobile banking, digital payment applications, and fintech, have become a catalyst for transformation in the banking industry. Banks are adopting strategies of developing digital platforms, partnering with fintechs, and developing HR skills to cope with these changes. Although faced with challenges such as data security, complex regulations, and system integration, the implementation of digital technology has great potential to improve banking services and operational efficiency. This research also identifies the positive and negative impacts of digital technology implementation on banking performance, including changes in people's behaviour in managing their organisations and improved performance of MSMEs. By understanding the challenges and associated strategies, this research provides valuable insights into how digital technology is changing the modern banking landscape and demonstrates the need for banks to continue to adapt and utilise these technologies to improve their performance and deliver better services to their customers.